2014
DOI: 10.1038/ncomms6074
|View full text |Cite
|
Sign up to set email alerts
|

Fucose-based PAMPs prime dendritic cells for follicular T helper cell polarization via DC-SIGN-dependent IL-27 production

Abstract: Dendritic cells (DCs) orchestrate antibody-mediated responses to combat extracellular pathogens including parasites by initiating T helper cell differentiation. Here we demonstrate that carbohydrate-specific signalling by DC-SIGN drives follicular T helper cell (T FH ) differentiation via IL-27 expression. Fucose, but not mannose, engagement of DC-SIGN results in activation of IKKe, which collaborates with type I IFNR signalling to induce formation and activation of transcription factor ISGF3. Notably, ISGF3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 52 publications
5
78
1
Order By: Relevance
“…Previous works have demonstrated that DC-SIGN interacts with glycan structures from a variety of pathogens ranging from virus to fungi3. In fact DC-SIGN binds glycoconjugates from HIV4, coronavirus5, herpes simplex virus6, Helicobacter pylori 4, Mycobacterium tuberculosis 478, Candida albicans 9, as well as cancer-related glycans10. More recently, different papers have reported that DC-SIGN also interacts with glycans form parasites, thereby modulating the immune response.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have demonstrated that DC-SIGN interacts with glycan structures from a variety of pathogens ranging from virus to fungi3. In fact DC-SIGN binds glycoconjugates from HIV4, coronavirus5, herpes simplex virus6, Helicobacter pylori 4, Mycobacterium tuberculosis 478, Candida albicans 9, as well as cancer-related glycans10. More recently, different papers have reported that DC-SIGN also interacts with glycans form parasites, thereby modulating the immune response.…”
mentioning
confidence: 99%
“…The interaction of DC-SIGN with pathogens, triggers specific signaling events that modulate DC activity at various levels, influencing phagocytosis16, suppressing TLR-induced maturation of DCs15, internalizing pathogen-derived molecules12, modifying DC-adhesion and migration17 and antigen presentation181920, and regulating T-cell activation by DCs47. In addition, DC-SIGN has also been involved in the induction of anti-inflammatory signals that result in the induction of anergic T cells21.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the type of DCs responsible for inducing Tfh cell priming. A recent study reported that engagement of DC-SIGN by fucose-based PAMPs licenses DCs for inducing Tfh polarization (17). Such activated DCs produce IL-27, which is essential for Tfh polarization.…”
Section: Potential Impact Of Hiv Infection On Tfh Cell Differentiationmentioning
confidence: 99%
“…Further interactions between DC and/or B cells and transitional Tfh cells at the follicle borders, and then B cells with Tfh cells within the developing germinal centers (GCs), are thought to solidify and amplify the Tfh differentiation program leading to pools of mature or GC Tfh cells that control the GC B cell response. Several molecules have been demonstrated to control Tfh and GC Tfh development, including the cytokines IL-6, IL-27 (8), IL-21 (9), transcription factors STAT3 (10) and STAT4 (11), and membrane interactions between CD28/B7 (12) and ICOS/ICOSL (13, 14). However, other molecular interactions that may be required for the maintenance or amplification of the Tfh program are still not clear.…”
Section: Introductionmentioning
confidence: 99%